Star on Stormy Mountain - Lewis, Gill (Lewis, Gill. Puppy Academy., 2016)
"Everyone says Star is much too fast to be a sheepdog but when your mom is a sheepdog champion, what else can you be? When a lamb goes missing on a field trip to Stormy Mountain, Star races up to find it. But she soon discovers that the lamb isn't the only one who needs her help"--